Sweet cherry fruit quality by half-intensive orchard management - Thurzó, Sándor; Racskó, József; Dani, Mária; Drén, Gábor (Acta Agraria Debreceniensis, 2006)
We made our study on fruit quality in the summer of 2005 on 6 cultivars („Bigarreau Burlat”, „Germersdorfi 3”, „Germersdorfi 45”, „Katalin”, „Linda” and „Van”) in a half-intensive sweet cherry orchard in Siófok. We measured fruit diameter, fruit width, fruit height, stem length and stem weight, fruit and pit weight and total soluble solids content. There were large differences among cultivars in the datas. These differences are due to genetic fruit-characteristics, because all other conditions were the same. We harvested fruits by 3 cultivars two times to check their characteristics on two ripening phases. We examined on these cultivars all the above listed fruit quality parameters. With these data we can be informed about the role of later than optimal harvesting time and how big an effect it has on fruit quality.